Promosi Kesehatan Untuk Mencegah Miopi dan Komplikasinya Pada Murid SDN 2 Berkoh, Purwokerto - Alfi Muntafiah; Afifah Afifah; Octavia Permata Sari; Ika Murti Harini; Qodri Santosa (Jurnal Pengabdian Pada Masyarakat, 2018)
HEALTH PROMOTION FOR PREVENTING AND COMPLICATIONS MYOPIA IN STUDENTS OF SDN 2 BERKOH, PURWOKERTO. Myopia is the most common refractive disorder in school-aged children. These visual disorders need attention, because they can interfere with life and daily work, and also their intellectual development. This health promotion activity is conducted to improve knowledge and understanding about myopia and the efforts that must be done to maintain eye health. This activity was conducted on 140 students of 4th, 5th, and 6th grade of SDN 2 Berkoh Purwokerto, through counseling, training, giving module, leaflet and poster. Based on the T-test of the pre-post and post-test in each class, the p values obtained in grades 4,5 and 6 respectively p = 0.058; 0.588; and 0.074. Conclusion: this activity can increase students' knowledge of myopia, although the increase is not significant.